Towards a militant future for African feminism: Mariama Ba’s Legacy in disguise (2017)
It is generally acknowledged that the path toed by African feminism is different from that of Western feminism. In most cases, African feminism is known for its collaborative and inclusive approach; it sees men as partners in progress in the struggle for emancipation of African women, whereas Western feminism is adjudged exclusionist in approach. This has given rise to the claim that the precursors of African feminism adopted a subtle/non-combatant strategy in seeking freedom from oppressive African patriarchal tradition for African women. Some of the texts by the avant-gardes, including Marie- Claire Matip’s Ngoda (1954), Therese Kuoh-Moukoury’s Rencontres essentielles (1969) and Aminata Mai'ga Ka’s La Voie du salut suivi de Le Miroir de la vie (1985), only depict deplorable women’s conditions in Black Africa without actually suggesting the way out of the woods. Some, such as Evelyne Mpoudi-Ngo lie’s Sous la cendre le feu (1990) and Buchi Emecheta’s Joys of Motherhood (2005) on the other hand, have been remarked for the compromising ways in which they have suggested emancipation for African women. While Mariama Ba’s So Long a Letter and Scarlet Song can be classified into the latter category, it is expedient to comment that the writer indirectly predicted the militant future directions of African Feminism. This futuristic tendency is foregrounded in Scarlet Song where she creates an Aristocratic French White woman, Mireille, nurtured and educated in Africa, but in defence of womanhood resorts into violence and murder to break the shackles of intransigent African traditions and set herself free from the psychological burdens inherent in the customs. Some literatures on theories of violence trace the genesis of women’s violence to victimisation in intimate relationships. Such theories help to locate Mireille’s succumb to violence and murder to her victimisation in her multiracial marriage. Although Mireille is non-African by birth, Mariama Ba creates this character to pave the way and act as ombudsman to teach the timid African woman the fact that violence must beget violence if the latter aspires to be absolutely free from hegemonic oppression. This is artistic creation partially borrows from the Western Feminist world to advocate militancy and violence which new generation of African feminists in the likes of Ken Bugul, Calixthe Beyala, Fatou Keita, and Lola Shoneyin currently demonstrate in their feminist discourse.